Produk Intangible Wisata Budaya sebagai Representator Nilai Budaya Osing di Kabupaten Banyuwangi - Hanggraito, Ahmadintya Anggit; Jemi Cahya Adi Wijaya; Randhi Nanang Darmawan (Jurnal Media dan Komunikasi, 2025)
The Osing culture remains one of the enduring local identities in Banyuwangi Regency amidst the forces of globalization. The uniqueness of the Osing people's traditions, arts, language, and indigenous knowledge presents a significant potential for the development of cultural tourism products. This study aims to explore the cultural values of the Osing that can be represented in intangible cultural tourism products in Banyuwangi Regency. The design of this research is descriptive with a qualitative approach. The findings reveal that Osing cultural values are reflected in various forms of cultural tourism products, such as traditional ceremonies, agricultural customs, performing arts, language, traditional food, and local medicine. These values serve as the core of the cultural tourism appeal in Banyuwangi. Cultural festivals like B-Fest play a vital role in the preservation and promotion of Osing culture through active participation from the local community. Thus, Osing culture not only strengthens local identity but also serves as a strategy for sustainable tourism development.